Pelatihan Motivasi Berprestasi Untuk Menurunkan Kecenderungan Prokrastinasi Akademik Mahasiswa Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Magelang - Yuhenita, Nofi Nur (Universitas Ahmad Dahlan, 2015)
Â Â Â Â The aim of this research is to discover the influence of achievement motivation training to the decr ease of studentâs tendency of academic procrastination. The design of this research is pre test post test control group design experiment. Subjek in this research is 20 people for experiment group and 20 people for the control group. The data analysis are t paired sample test that was used to test the differences between the pre-test and post-test result of achievement motivation training given to either experiment and t independent sample to test the difference between the Â gain score pre-post test of experiment group and control group after the students conducted the achievement motivation training. The result of the research shows that there are significant differences of studentâs academic procrastination for those who conduct the training and the others who did not conduct the training. Finally, this research concludes that achievement motivation training can be used to decrease studentâs academic procrastination. This research can be used by all stakeholders, Unit Pelaksana Teknis Layanan Bimbingan dan Konseling, lecturer, counselor at the college to reduce the tendency of academic procrastination by providing training on student achievement motivation.Â